Business as unusual: medical oncology services adapt and deliver during COVID‐19. Issue 5 (27th May 2021) - Travers, Avraham; Adler, Kim; Blanchard, Gillian; Bonaventura, Tony; Charlton, Julie; Day, Fiona; Healey, Laura; Kim, Sang; Lombard, Janine; Mallesara, Girish; Mandaliya, Hiren; Navani, Vishal; et al.
Abstract: Background: The COVID‐19 pandemic has challenged cancer care globally, introducing resource limitations and competing risks into clinical practice. Aims: To describe the COVID‐19 impact on medical oncology care provision in an Australian setting. Methods: Calvary Mater Newcastle and Newcastle Private Hospital medical oncology data from 1 February to 31 April 2019 versus 2020 were retrospectively analysed. Results: Three hundred and sixty‐four inpatient admissions occurred in 2020, 21% less than in 2019. Total inpatient days decreased by 22% (2842 vs 2203). April was most impacted (36% and 44% fewer admissions and inpatient days respectively). Mean length of stay remained unchanged (6.4 vs 6.2 days, P = 0.7). In all, 5072 outpatient consultations were conducted, including 417 new‐patient consultations (4% and 6% increase on 2019 respectively). Telephone consultations (0 vs 1380) replaced one‐quarter of face‐to‐face consultations (4859 vs 3623, −25%), with minimal telehealth use (6 vs 69). Day Treatment Centre encounters remained stable (3751 vs 3444, −8%). The proportion of new patients planned for palliative treatment decreased (35% vs 28%, P = 0.04), observation increased (16% vs 23%, P = 0.04) and curative intent treatment was unchanged (both 41%). Recruiting clinical trials decreased by one‐third (45 vs 30), two trials were activated (vs 5 in 2019) and 45% fewer patients consented to trial participation (62 vs 34). Conclusion: Our medical oncology teams adapted rapidly to COVID‐19 with significant changes to care provision, including fewer hospital admissions, a notable transition to telephone‐based outpatient clinics and reduced clinical trial activity. The continuum of care was largely defended despite pandemic considerations and growing service volumes.